2009
DOI: 10.2139/ssrn.1991870
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Short-Term Impact of Pension Reforms on Older Workers’ Participation Rates in the EU: A Diff-in-Diff Approach

Abstract: Assessing the short-term impact of pension reforms on older workers' participation rates in the EU: a diff-in-diff approach

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Figures for Britain in 2013, showed that 42% of women were employed on a part-time basis in comparison with only 13% of men and women’s pay is also consistently lower than men [ 56 ]. Women over 50 have been long shown to have more discontinuous employment histories than men as a result of breaks associated with having children [ 3 , 18 ]. This results in fewer chances to climb up the career ladder for women, which is closely related to pension entitlements and subsequent retirement choices.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figures for Britain in 2013, showed that 42% of women were employed on a part-time basis in comparison with only 13% of men and women’s pay is also consistently lower than men [ 56 ]. Women over 50 have been long shown to have more discontinuous employment histories than men as a result of breaks associated with having children [ 3 , 18 ]. This results in fewer chances to climb up the career ladder for women, which is closely related to pension entitlements and subsequent retirement choices.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, for women in particular, any lack of opportunities to take on more flexible bridge employment could act as a potential barrier to EWL. Similarly, the short-term effect of pension reform in Europe for 50–64 year olds has found that, due to the differing lengths of time that women and men spend in employment and the more stable career paths of males compared to females, pension reforms have resulted in a short-term positive impact on female participation, compared to a modest reduction in male participation [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other instruments such as flexible retirement or the possibility to combine pension and work give more choice for people's retirement transitions (D'Addio, 2014; see also Ebbinghaus, 2006, 2012). Although latest pension reforms, especially those aiming at postponing labour market exit, are considered incremental rather than radically changing the pension system design (Arpaia, Dybczak, & Pierini, 2009), they make adequate old age income much more dependent on employment and earnings throughout the working life, but specifically at its tail end. This, in turn, reinforces existing inequalities in working life during retirement.…”
Section: The Policy Context Of Extending Working Livesmentioning
confidence: 99%
“…Whereas studies have found that reforming exit pathways can effectively increase employment of older workers (Arpaia et al, 2009; Ebbinghaus and Hofäcker, 2013), such reforms are not without risks or side‐effects. In the “heydays” of early retirement, Casey (1987) observed that when closing off one exit pathway there is a risk that older workers will start using other exit schemes that, as a result of such reforms, become relatively more accessible or attractive.…”
Section: Introductionmentioning
confidence: 99%